Question
upstudy study bank question image url

Given that \( \cos \theta=\frac{8}{17} \cdot \operatorname{col} \) culate \( \frac{\sin ^{2} \theta+\cos ^{2} \theta}{\sin \theta+\cos \theta} \) \( \frac{\cos \theta}{\sin \theta} \)

Ask by Stanley Stuart. in Nigeria
Feb 17,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The results are: 1. \( \frac{17}{23} \) 2. \( \frac{8}{15} \)

Solution

To solve the problem, we start with the known condition: 1. \( \cos \theta = \frac{8}{17} \) We need to calculate two expressions: 1. \( \frac{\sin^2 \theta + \cos^2 \theta}{\sin \theta + \cos \theta} \) 2. \( \frac{\cos \theta}{\sin \theta} \) ### Step 1: Calculate \( \sin \theta \) Using the Pythagorean identity: \[ \sin^2 \theta + \cos^2 \theta = 1 \] Substituting \( \cos \theta \): \[ \sin^2 \theta + \left(\frac{8}{17}\right)^2 = 1 \] Calculating \( \left(\frac{8}{17}\right)^2 \): \[ \left(\frac{8}{17}\right)^2 = \frac{64}{289} \] Now substituting back into the identity: \[ \sin^2 \theta + \frac{64}{289} = 1 \] To isolate \( \sin^2 \theta \): \[ \sin^2 \theta = 1 - \frac{64}{289} = \frac{289}{289} - \frac{64}{289} = \frac{225}{289} \] Taking the square root to find \( \sin \theta \): \[ \sin \theta = \sqrt{\frac{225}{289}} = \frac{15}{17} \] ### Step 2: Calculate the first expression Now we can calculate: \[ \frac{\sin^2 \theta + \cos^2 \theta}{\sin \theta + \cos \theta} \] We already know \( \sin^2 \theta + \cos^2 \theta = 1 \), so we need to find \( \sin \theta + \cos \theta \): \[ \sin \theta + \cos \theta = \frac{15}{17} + \frac{8}{17} = \frac{23}{17} \] Now substituting into the expression: \[ \frac{1}{\frac{23}{17}} = \frac{17}{23} \] ### Step 3: Calculate the second expression Now we calculate: \[ \frac{\cos \theta}{\sin \theta} = \frac{\frac{8}{17}}{\frac{15}{17}} = \frac{8}{15} \] ### Final Results Thus, the final results are: 1. \( \frac{\sin^2 \theta + \cos^2 \theta}{\sin \theta + \cos \theta} = \frac{17}{23} \) 2. \( \frac{\cos \theta}{\sin \theta} = \frac{8}{15} \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

Let's start with the first part of your calculation. Since we know that \( \cos^2 \theta + \sin^2 \theta = 1 \), we can use that to simplify our expression. 1. We know \( \cos \theta = \frac{8}{17} \), so we can find \( \sin \theta \) using the identity: \[ \sin^2 \theta = 1 - \cos^2 \theta = 1 - \left(\frac{8}{17}\right)^2 = 1 - \frac{64}{289} = \frac{225}{289}. \] Thus, \( \sin \theta = \frac{15}{17} \) (since sine is positive in the first quadrant). 2. Now we can add \( \sin^2 \theta \) and \( \cos^2 \theta \): \[ \frac{\sin^2 \theta + \cos^2 \theta}{\sin \theta + \cos \theta} = \frac{1}{\sin \theta + \cos \theta}. \] Then we need to calculate \( \sin \theta + \cos \theta \): \[ \sin \theta + \cos \theta = \frac{15}{17} + \frac{8}{17} = \frac{23}{17}. \] Therefore, \[ \frac{\sin^2 \theta + \cos^2 \theta}{\sin \theta + \cos \theta} = \frac{1}{\frac{23}{17}} = \frac{17}{23}. \] Next, let’s tackle the second part to find \( \frac{\cos \theta}{\sin \theta} \): \[ \frac{\cos \theta}{\sin \theta} = \frac{\frac{8}{17}}{\frac{15}{17}} = \frac{8}{15}. \] In conclusion, we have: 1. \( \frac{\sin^2 \theta + \cos^2 \theta}{\sin \theta + \cos \theta} = \frac{17}{23} \) 2. \( \frac{\cos \theta}{\sin \theta} = \frac{8}{15} \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy